2016
DOI: 10.1007/s10903-016-0449-4
|View full text |Cite
|
Sign up to set email alerts
|

The Relation Between Discrimination, Sense of Coherence and Health Varies According to Ethnicity: A Study Among Three Distinct Populations in Israel

Abstract: Self-reported experiences of discrimination and sense of coherence (SOC) have been found to be associated with health. A face-to-face survey of Long Term Jewish Residents (LTJR), Arabs and former Soviet Union (fSU) immigrants in Israel was performed. Respondents reported their physical and mental health, self-reported experiences of discrimination, SOC and socioeconomic status. Multivariable logistic regressions and bootstrapping path analyses were performed. Discrimination was associated with health after adj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 45 publications
(68 reference statements)
0
4
0
Order By: Relevance
“…A different study showed that Jewish landlords are 2.4 times more likely to confirm the availability of property when the caller is Jewish rather than an Arab potential renter [55]. Given past research, which showed a direct association between perceived discrimination and multiple negative outcomes, including higher levels of depressive symptoms [56], smoking [22], and poorer health [57], addressing sense of discrimination in this population is highly important.…”
Section: Discussionmentioning
confidence: 99%
“…A different study showed that Jewish landlords are 2.4 times more likely to confirm the availability of property when the caller is Jewish rather than an Arab potential renter [55]. Given past research, which showed a direct association between perceived discrimination and multiple negative outcomes, including higher levels of depressive symptoms [56], smoking [22], and poorer health [57], addressing sense of discrimination in this population is highly important.…”
Section: Discussionmentioning
confidence: 99%
“…This group is distinctive culturally, having a different language (Arabic), affiliating mostly with the Muslim religion, and having autonomous institutions in various domains such as mass media, religion and education (Smooha, 1997 ). Thought PCIs are full citizens of Israel, they are disadvantaged in education and other social-economic indicators, relative to veteran Jews, and are frequently discriminated against (Baron-Epel, Berardi, Bellettiere, & Shalata, 2017 ; Haberfeld & Cohen, 2007 ; Lissitsa & Chachashvili-Bolotin, 2019 ). Due to lower educational attainment and previous findings on health literacy among Israeli groups (Levin-Zamir et al, 2016 ), PCI are expected to have lower health literacy.…”
Section: Group Differences In Health and Ehealth Literaciesmentioning
confidence: 99%
“…Palestinian Citizens of Israel (PCI) are an ethnic minority that constitute 21% of the country’s population, most of them Muslims [ 37 ]. They experience social exclusion and discrimination [ 38 , 39 , 40 ], resulting in higher rates of poverty and lower educational attainment [ 37 ]. PCI differ from the Jewish majority in language, religion, and other cultural characteristics [ 41 , 42 ].…”
Section: Introductionmentioning
confidence: 99%